Pitfalls in graft survival analysis - Unterrainer, Christian; Döhler, Bernd; Süsal, Caner (HLA, 2018)
The reliability of a scientific work depends on the accuracy of the analysis. Scientific publications in the field of kidney transplantation still contain methodical errors that may lead to wrong conclusions and result in severe consequences for the patients. Using the data from the Collaborative Transplant Study, we are presenting in this study six examples of the erroneous usage of statistical methods and show how these mistakes can be avoided.
Gesehen am 21.02.2020
: Published online: 5 December 2017